Dentofacial effects of miniscrew-anchored maxillary protraction on prepubertal children with maxillary deficiency: a randomized controlled trial - Ahmed Mohamed Kamel; Nour Eldin Tarraf; Ahmed Maher Fouda; Ahmad Mohammed Hafez; Ahmed El-Bialy; Benedict Wilmes (SpringerOpen, 2023)
Abstract Background The introduction of bone-anchored maxillary protraction eliminated the side effects of facemask in the early treatment of patients with maxillary retrusion. This study aimed to evaluate the effects of miniscrew-anchored maxillary protraction (MAMP) and compare them with the growth changes in an untreated control group in growing patients with Class III malocclusion. Methods Forty growing patients with Class III malocclusion and retrognathic maxilla were randomly allocated into two groups: treated and control groups. In the treated group, patients were treated with full-time intermaxillary Class III elastics (C3E) anchored by a hybrid hyrax (HH) in the maxilla and a bone-supported bar in the mandible. Protraction was stopped after obtaining a positive overjet. Cephalometric radiographs were acquired before and after the treatment. Data were statistically analyzed on an intention-to-treat basis. Intergroup comparisons were also made using analysis of covariance with the readings at T0 as a covariate. Results Forty patients agreed to participate, and 30 of them completed the study (treated group, n = 17; control group, n = 13). The average treatment duration was 11.9 months. MAMP resulted in a significant maxillary advancement (A-VR, 4.34 mm) with significant control over the mandibular growth. No significant increase in the mandibular plane angle was found in the treated group compared with the control group. The upper and lower incisors showed significant protrusion in the treated group. Conclusions Within the limitations of this study and high attrition rate, the MAMP protocol can effectively increase maxillary forward growth with good control over the growth of the mandible antero-posteriorly and vertically.